SOSIALISASI CARA MENINGKATKAN MINAT MEMBACA BUKU CERITA ANAK-ANAK PADA USIA 2-3 TAHUN DI DUSUN NGINJEN KECAMATAN DEKET KABUPATEN LAMONGAN - Sustyorini, Emalia Nova (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2017)
ABSTRACT This study aims at describing ways and parents’ role in developing students’ reading interest in reading story book age 2-3 year in Dusun Nginjen Kecamatan Deket Kabupaten Lamongan. This study employs descriptive qualitative in nature. This research concerns on how to promote children’s story book age 2-3 ini Dusun Nginjen Kecamatan Deket Kabupaten Lamongan. This research takes place in Lamongan. Meanwhile, the techniques of data collecting are observation, recording, and transcribing. The results showed some ways to develop students’ reading interest are as follows: visiting library, purchasing story books, getting the students used to read books before going to bed, and providing facilities for the children to read including cozy and comfortable place to read. Finally. A recommendation is given to parents to promote students reading habit by doing activities such as reading book habit, purchasing various story books and running a program what so called 1821 the program run by Pemda Lamongan.